Wild and wrangled - Sage, Lyla (Sage, Lyla. Rebel Blue Ranch novel, 2025)
"Camille Ashwood had always loved a plan. Her latest was her best yet. She was going to get married so she could secure her daughter's future, get her overbearing parents off her back, and finally start building her own life in small town Meadowlark, Wyoming. Easy, right? But when her groom doesn't show up to the wedding, Cam's life is turned upside down--she doesn't even have a place to live. That is, until she finds out the house she's loved since high school is available to rent. There's only one problem: the neighbor. Dusty Tucker has spent nearly all of his adult life running. Running from what, though? More like who: Cam Ashwood. But ever since he returned home last year, the girl who was his first, well, everything has become a woman seemingly determined to keep him at arm's length. And he was okay with that--at least, that's what he kept telling himself. She was getting married, after all. But now she's single and living next door. Dusty wants to show her that they can be friends, and that he can stay put. Despite her best attempts to stay far away from Dusty Tucker, Cam realizes that being close to him is like slipping on her favorite jeans. Easy. Comfortable. That is until past wounds start to open and feelings-both old and new-wreak havoc. Nearly ten years after they first met, Dusty and Cam begin to wonder if their first love can also be their last. And this time, will it be forever?"--